The Role of Regional Government in Controlling the Conversion of Agricultural Land to Housing Growth in Sragen Regency - Najma Kusumawardhani Mustika Putri; Ratih Damayanti (Law Research Review Quarterly, 2026)
The growth of housing development in Sragen Regency, an agricultural region, has put pressure on the sustainability of agricultural land. This study aims to analyze housing growth and assess the role of local governments in controlling agricultural land conversion. The research method used is a juridical-empirical legal research with a qualitative approach. Data were obtained through interviews with relevant regional officials, legislation, and literature reviews. The results show that housing development reaches approximately 1,000 units per year, while the level of fulfillment of new housing needs is approximately 87% with a backlog of approximately 28,000 units. The local government has carried out a controlling role through spatial planning instruments, spatial utilization permits, the Suitability of Spatial Utilization Activities (KKPR), as well as coordination between regional officials and the provision of incentives to farmers. However, this role has not been optimal due to a disconnect between the role conception as formulated in spatial planning policies and regulations and the implementation of the local government's role in controlling agricultural land conversion in the field.